A cellulose nanofiber–polyacrylamide hydrogel based on a co-electrolyte system for solid-state zinc ion batteries to operate at extremely cold temperatures. Issue 45 (15th November 2021) - Xu, Wangwang; Liu, Chaozheng; Ren, Suxia; Lee, Danbee; Gwon, Jaegyoung; Flake, John C.; Lei, Tingzhou; Baisakh, Niranjan; Wu, Qinglin
Abstract : A cellulose nanofiber (CNF)–polyacrylamide (PAM) hydrogel electrolyte is developed. It has the potential to expand the application of ZIBs to broad fields such as wind turbines in desolate areas, cold polar regions, and aerospace. Abstract : Solid-state zinc ion batteries (ssBs) based on hydrogel electrolytes have received tremendous attention due to their reliable safety, high flexibility and robust performance. However, freezing of the hydrogel electrolyte and resulting low ionic conductivity limit the capability of ssBs to work at low temperatures. Herein, a wood based cellulose nanofiber (CNF)–polyacrylamide (PAM) hydrogel electrolyte was developed with a hybrid methanol/water solvent. At the optimized methanol molar ratio of 56% (Me56), the hybrid electrolyte shows a low freezing point and high-Zn 2+ reversibility. The reversibility of the Zn anode is boosted in this antisolvent since Zn 2+ solvation is weakened and corrosion reactions are suppressed. With the Me56 hybrid electrolyte, MgVO/Zn batteries can deliver a high specific capacity of 214 mA h g −1 after 4000 cycles at 10 A g −1 (charging time: about 1 minute). The developed CNF–PAM hydrogel maintains high flexibility under repeated bending and twisting under very cold conditions. At an extremely low temperature of −60 °C, the ssBs still deliver a high specific capacity of about 140 mA h g −1 at 10 mA g −1 while remaining flexible, exhibiting great potential to be applied in wearable devices under cold conditions.